Hak Uji Materiil oleh Mahkamah Agung untuk Menguji Peraturan Perundang-Undangan di Bawah Undang-Undang di Indonesia - Arie Satio Rantjoko (Fakultas Hukum Universitas Islam Jember, 2014)
Indonesian system is divided into three powers as the President of the House of Representatives as the executive legislative and judicial branches of government as the Supreme Court have each possess its own function which should not overlap because if there is one power of the power to interfere with duties or functions of other powers then there is a duality of power functions. To avoid dualism test regulations under the authority of law is conceptually the first test against legislation both legislation and regulations under the law should be left entirely to the judiciary based on the concept of power-sharing as stipulated in the Act Constitution of the Republic of Indonesia after the 1945 amendment.